Metabolic Dysregulation Induced in Plasmodium falciparum by Dihydroartemisinin and Other Front-Line Antimalarial Drugs. (6th July 2015) - Cobbold, Simon A.; Chua, Hwa H.; Nijagal, Brunda; Creek, Darren J.; Ralph, Stuart A.; McConville, Malcolm J.
Abstract : Detailed information on the mode of action of antimalarial drugs can be used to improve existing drugs, identify new drug targets, and understand the basis of drug resistance. In this study we describe the use of a time-resolved, mass spectrometry (MS)–based metabolite profiling approach to map the metabolic perturbations induced by a panel of clinical antimalarial drugs and inhibitors on Plasmodium falciparum asexual blood stages. Drug-induced changes in metabolite levels in P. falciparum –infected erythrocytes were monitored over time using gas chromatography–MS and liquid chromatography–MS and changes in specific metabolic fluxes confirmed by nonstationary [ 13 C]-glucose labeling. Dihydroartemisinin (DHA) was found to disrupt hemoglobin catabolism within 1 hour of exposure, resulting in a transient decrease in hemoglobin-derived peptides. Unexpectedly, it also disrupted pyrimidine biosynthesis, resulting in increased [ 13 C]-glucose flux toward malate production, potentially explaining the susceptibility of P. falciparum to DHA during early blood-stage development. Unique metabolic signatures were also found for atovaquone, chloroquine, proguanil, cycloguanil and methylene blue. We also show that this approach can be used to identify the mode of action of novel antimalarials, such as the compound Torin 2, which inhibits hemoglobin catabolism.